Evaluating final-year student classroom communication at the faculty of engineering and built environment, Universiti Kebangsaan Malaysia - Muhammad Faiz Bukhori,; Muhammad Farihan Irfan Mohd Nor,; Abdul Halim Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Classroom communication is a very important and complex aspect in teaching and learning. The complexity of a communication process is attributed to a host of components that include the participants, messages, encoding, decoding, and transmission channels. Not much is currently known concerning classroom communication in the context of engineering education in Malaysian universities. This paper evaluates classroom communication of final-year students of the Electrical and Electronic engineering degree programs at Universiti Kebangsaan Malaysia. Four important aspects of classroom communication were investigated to understand student abilities and issues in classroom communication. One hundred and four students undertook the self-administered survey, yielding a response rate of 92.8%. The majority of the students exhibited good non-verbal communication practices, and scored favourably in the aspect of adapting the way they communicate to others. However, 42.3% of the respondents seemed to have difficulties to explain and express ideas confidently via classroom presentations. Additionally, 43 students (41.3%) appeared to be handicapped in participating actively in class discussions. Finally, at least 40 respondents (38.5%) reported difficulties to express ideas in English, but not to the extent of hindering them in participating in classroom discussions. Further studies are needed to uncover classroom communication issues in student learning among engineering students at Universiti Kebangsaan Malaysia.